2008
DOI: 10.1109/tcapt.2008.2001162
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Surface Wear and Contact Resistance During the Fretting of <emphasis emphasistype="italic">In-Vivo</emphasis> Electrical Contacts

Abstract: Abstract-A study of the high frequency intermittency events occurring during the fretting of contact surfaces used for in-vivo electronic systems, is presented. The emphasis of the study is to determine and the relationship between the contact resistance during the fretting process and to relate this to surface wear, as a function of the applied force. The emphasis is on fretting experiments in the crossed rod configuration with a range of contact forces, between 1.75 and 0.05 N.An established test system and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Researchers have studied the dynamic characteristics of ECR through experimental and analytical techniques [8,[12][13][14]. When electrical connectors were placed under cyclic motion with relatively small amplitude, the contacting electrodes' surface developed fretting wear and the enlarged slip amplitude led to faster increase in ECR [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have studied the dynamic characteristics of ECR through experimental and analytical techniques [8,[12][13][14]. When electrical connectors were placed under cyclic motion with relatively small amplitude, the contacting electrodes' surface developed fretting wear and the enlarged slip amplitude led to faster increase in ECR [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have studied the dynamic characteristics of ECR through experimental and analytical techniques [8,[12][13][14]. When electrical connectors were placed under cyclic motion with relatively small amplitude, the contacting electrodes' surface developed fretting wear and the enlarged slip amplitude led to faster increase in ECR [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The research group in Lyon, France, focused on studying load conditions and showed the relationship between sliding behaviour at the interface and the service life of electrical contacts [10,11]. In Great Britain, McBride's Southampton electromechanical group studied in detail the relationship between surface damage and intermittent contact resistance errors [12,13]. This group also performed unique in situ measurements of temperature, humidity and pressure in automotive connectors, which provided a better understanding of the actual operating conditions of these components [14].…”
Section: Introductionmentioning
confidence: 99%